Special issue of 'Composer' (Journal of the Composer's Guild of Great Britain) (International Library of African Music, 1965)
The April 1966 Issue of the quarterly music journal ‘Composer’ may be of special interest to you. It will contain papers delivered at the Conference of Music and Education in the Commonwealth, held at the University of Liverpool in September 1965, as part of the Commonwealth Festival. This material will be invaluable for students, musicians, anthropologists and those concerned with music education, as it gives a unique view of the various musical cultures of the Commonwealth.
Keywords: African Music